2009
DOI: 10.1177/0269881109102606
|View full text |Cite
|
Sign up to set email alerts
|

A single high dose of escitalopram increases mismatch negativity without affecting processing negativity or P300 amplitude in healthy volunteers

Abstract: Information processing deficits are commonly found in psychiatric illnesses, while at the biochemical level serotonin seems to play a role in nearly all psychiatric disorders. Processing negativity (PN), mismatch negativity (MMN) and P300 amplitude are electrophysiological measures of information processing. The present study was designed to replicate and further extent the results of our initial study on the effects of a low dose of escitalopram (10 mg) on MMN, PN and P300 amplitude. In a randomised, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 55 publications
6
37
0
Order By: Relevance
“…The study by Van Laar et al mentioned above also included the SSRI paroxetine (30 mg) and the non-specific 5-HT2 antagonist nefazodone (200 mg) but did not find any effect. Consistent acute nil effects have also been reported for 15 mg escitolapram (Wienberg et al, 2010), as well as in older studies using methysergide (Meador et al, 1989), and fenfluramine (Pritchard et al, 1987). Inconsistently, McAllister-Williams et al (2002) found larger P300s after ATD.…”
Section: 'Attention' and Memory Updating: P300supporting
confidence: 77%
“…The study by Van Laar et al mentioned above also included the SSRI paroxetine (30 mg) and the non-specific 5-HT2 antagonist nefazodone (200 mg) but did not find any effect. Consistent acute nil effects have also been reported for 15 mg escitolapram (Wienberg et al, 2010), as well as in older studies using methysergide (Meador et al, 1989), and fenfluramine (Pritchard et al, 1987). Inconsistently, McAllister-Williams et al (2002) found larger P300s after ATD.…”
Section: 'Attention' and Memory Updating: P300supporting
confidence: 77%
“…For the P3, it has repeatedly been shown that this component does not depend on the serotonergic system (e.g. Oranje et al, 2008;Wienberg et al, 2009). The pattern observed for the Pe nicely fits to this.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects were examined with the Copenhagen Psychophysiology Test Battery (CPTB) Jensen et al, 2008;Wienberg et al, 2010). The CPTB includes PPI, P50 suppression, mismatch negativity (MMN), and selective attention paradigms.…”
Section: Psychophysiologymentioning
confidence: 99%